THE CURRENT STATE AND PROSPECT OF DEVELOPMENT OF METHODS OF CONTINUOUS DIAGNOSTICS OF THE CONDITION OF HIGH-VOLTAGE ELECTRIC MOTORS ON JSC «BSW MANAGEMENT COMPANY OF HOLDING «ВМС» - N. A. Samsonov; V. S. Zakharenko (Литьë и металлургия, 2015)
Transition from system of planned and compulsory repairs, to service of the equipment in connection of its current technical condition is one of the main directions in resource saving.